International trade and labour's class struggles : political economic determinants of labour protests - Mack, Vincent Zhi Wei (2015)
Explanations of labour protests and strikes have thus far always approached the issue from a social movement/interest organizational level constrain within a national level environment. Despite the fact that a portion of these protests being occur as a result of losing out from international trade liberalization, the influence of international factors within these studies have been absent, or minimal. Putting together sociological and political science theories of protests with theories on international trade, I argue that international trade exposure creates the political economic conditions for protest through altering labour's access to economic opportunities. This however, is moderated by the political opportunity structures that are specific to individual countries. Using a quantitative regression analyses, this dissertation found that labour protests tend to happen when the economic interests of labour are threatened. Also, the presence of elements within the political opportunity structure - particularly union funding and institutionalised labour rights - has a moderating effect on the emergence of these labour protests.